Bedukmawa: Marketplace and Fintech Design for Student Entrepreneurship in the Industrial Revolution 4.0 Era - Suryo Pratolo (Universitas Muhammadiyah Yogyakarta, Indonesia, 2020)
Research Aims: The buying and selling system can no longer be manual instead it must be based on information technology so that it can be accepted by millennials and make them have a strong entrepreneurial spirit. For this reason, the movement of “Belabeli Produk Mahasiswa” (Bedukmawa) offers solutions to millennial generation the entrepreneurial challenges. Bedukmawa is an entrepreneurial movement based on demand-pull or pulling needs with incentives from the campus to encourage the buying movement by students to other students, so that with this transaction movement there will be a producing and selling movement naturally. The producing and marketing actions are the atmosphere that is raised on campus so that the university has a role in making it happen by providing stimulative funds for it. Bedukmutu is a web-based application that uses the concept of IoT (Internet of Things) that upholds convenience and public acceptance for millennial generation students. Hence, the purpose of this study is to obtain direction on entrepreneurship design on the campus that can encourage students to practice entrepreneurship effectively and efficiently in the era of the industrial revolution 4.0.Design/Methodology/Approach: In evaluating the Bedukmawa operation, we involve some users to conduct Focus Group Discussion (FGD), they were academic community groups, namely the lecturer group and the university leadership group.Research Findings: The results of applying this Bedukmawa application for a year at University Muhammadiyah Yogyakarta as an object of research produced an extraordinary output, in which the student entrepreneurship movement has reached billions of rupiahs monthly and with this application, IoT Big Data is presented, in which it provides various measurable information in multiple ways.Theoretical contribution/Originality: This paper is an initial research that discusses how policies in creating a marketplace in campus using a web-based application can be integrated with entrepreneurial learning practices for students.Practitioner/Policy implication: This paper provides a practical overview related to how the marketplace can be formed in a campus environment using a web-based application so that it can support students to learn entrepreneurship in a real way.Research limitation/Implication: This paper only provides a framework based on one of private campus experiences in Indonesia. Replication of this policy on other campuses may require certain adjustments given the environment and culture of each campus is different.